Dietary supplementation with fermented rapeseed and seaweed modulates parasite infections and gut microbiota in outdoor pigs - Bonde, Charlotte Smith; Drøhse, Frida Brasen; Büdeyri Gökgöz, Nilay; Krych, Lukasz; Nielsen, Dennis Sandris; Petersen, Heidi Huus; Matthiesen, Rikke; Pedersen, Ninfa Rangel; Geldhof, Peter; Williams, Andrew R.; Thamsborg, Stig Milan; Mejer, Helena (Frontiers in Veterinary Science, 2025)
Outdoor pig production systems can increase exposure to helminth infections such as Ascaris suum. Anthelmintic drug treatments are currently the primary strategy for controlling such infections; however, this approach is considered unsustainable due to the risk of parasites developing anthelmintic resistance. This study investigated the potential anthelmintic effect of a 2% w/w fermented rapeseed–seaweed (FRS) dietary supplement administered over an 11–12 week period in growing-finisher pigs. Outcomes assessed included parasitic fecal egg counts (FEC), serology, gut microbiota composition, and systemic inflammation. The FRS supplement consisted of 6% Saccharina latissima, 6% Ascophyllum nodosum, and 88% rapeseed meal (based on dry matter) and was provided in two different batches. Supplementation with FRS tended to lower FEC and reduce the incidence of A. suum infection. However, this effect varied between batches. FRS also influenced gut microbiota composition: pigs that were fed the second batch of FRS showed an increased relative abundance of several Bacteroidetes members (e.g., Prevotella), while unsupplemented pigs were enriched with various taxa from the Firmicutes phylum, such as Clostridium spp. Furthermore, pigs fed the second batch of FTR showed reduced daily weight gain compared to those fed the control diet. Overall, our results indicate that FRS modulates the gut microbiota toward a composition potentially associated with improved gut health and may have promise as a prebiotic or novel feed additive to help reduce helminth infections.